Pengaruh DAR, CR, dan NPM Terhadap Harga Saham Perusahaan Telekomunikasi yang Terdaftar di BEI - Arum Dektaria; Ratna Yunita (Niqosiya: Journal of Economics and Business Research, 2023)
Introduction: The information obtained through the study of financial statements can be used to describe a company's performance. Investors need the results of financial statement analysis as a basis for making investment decisions because stock price movements can be seen by observing them. The share price, according to theory, will fall as the value of DAR increases. Meanwhile, if the CR and NPM values increase, the stock price will increase. However, after collecting research data, it was found that there was a discrepancy in data facts according to theory. Research Methods: This study adopts a quantitative associative research methodology. In the sampling technique, a purposive sampling technique was used, and four telecommunications businesses were taken as samples. By using MS Excel 2010 and Eviews 9 software, the research approach uses panel data analysis, starting with evaluating panel data estimation methods and continuing with selecting panel data regression models, testing classical assumptions, and testing hypotheses. Results: Based on the research above, it was found that the best estimation model chosen was the Fixed Effect Model (FEM). Furthermore, using the best choice model, classical assumption testing is carried out and the result is that the classical assumption obligation has been fulfilled. Conclusion: The results of this study, partially DAR has no significant effect on stock prices, CR has a significant effect on stock prices, and NPM has a significant effect on stock prices. Meanwhile, DAR, CR and NPM simultaneously have a significant influence on the stock prices of Indonesian telecommunications companies listed on the Indonesia Stock Exchange from 2017 to 2021.